Active and Passive Risk-Taking - Christian König-Kersting; Johannes Lohse; Anna Merkel (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
Risk-taking may depend on whether risks result from an action (active risk-taking) or from not taking action (passive risk-taking). We develop a new experimental risk-elicitation procedure, the Dynamic Lottery Adjustment Task, and employ it across two separate experiments to study the size and direction of potential mode-of-choice effects (i.e. differences in risk-taking between active and passive decision modes). While our tightly controlled lab study provides little evidence for such effects, we find substantial evidence for mode-of-choice effects when decisions are spread out over 10 days and attention costs are a key feature of the online choice environment we use.
Keywords: D81; D91; C91; 330; risk-taking; mode-of-choice; status quo effect; omission bias